Structure and floristic composition associated with an endangered species Beta patula Aiton (Amaranthaceae) in the Islands of Madeira Archipelago - Nóbrega, Humberto (2021)
Twenty-two native Crop Wild Relatives (CWR) occur in specific dry environments of Madeira Archipelago, like Desembarcadouro islet in Ponta de São Lourenço and Chão islet in Desertas Islands. Nine of them share the same gene pool with crop species included in Annex I of the International Treaty on Plant Genetic Resources for Food and Agriculture. Amongst them, Beta patula Aiton, an IUCN Critically Endangered species, has been studied in detail for in situ and ex situ conservation. The present paper summarises the information recorded during the Beta patula population assessment. Valuable information on plant communities associated with this species was obtained.